2017
DOI: 10.1186/s12960-017-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Incentives to change: effects of performance-based financing on health workers in Zambia

Abstract: BackgroundPerformance-based financing (PBF) has been implemented in a number of countries with the aim of transforming health systems and improving maternal and child health. This paper examines the effect of PBF on health workers’ job satisfaction, motivation, and attrition in Zambia. It uses a randomized intervention/control design to evaluate before–after changes for three groups: intervention (PBF) group, control 1 (C1; enhanced financing) group, and control 2 (C2; pure control) group.MethodsMixed methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 63 publications
5
60
0
1
Order By: Relevance
“…The effects of PBF-N have been partly determined by problems at the level of these other interventions. This dependence upon the whole health system has been documented in many PBF studies; barriers vary across experiences, but several of those reported in this study (competencies of human resources at the facility level, skills of supervisors, supply of inputs and delays in payment) have been reported in other experiences [50][51][52][53][54][55][56][57][58][59][60]. Such a dependence confirms the systemic nature of PBF [61], but at short term, it has an impact on the effectiveness of the strategy.…”
Section: Discussionsupporting
confidence: 69%
“…The effects of PBF-N have been partly determined by problems at the level of these other interventions. This dependence upon the whole health system has been documented in many PBF studies; barriers vary across experiences, but several of those reported in this study (competencies of human resources at the facility level, skills of supervisors, supply of inputs and delays in payment) have been reported in other experiences [50][51][52][53][54][55][56][57][58][59][60]. Such a dependence confirms the systemic nature of PBF [61], but at short term, it has an impact on the effectiveness of the strategy.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, monitoring serves as an audit function to guard against gaming and overpayment . Importantly, performance‐adjusted payment rates have been shown to motivate health care providers to align their health care services (outcomes) with the performance requirements, especially quality …”
Section: Discussionmentioning
confidence: 99%
“…Existing empirical evidence has demonstrated that efforts to build the management capacity in health facilities and of health teams can improve the performance of LMICs' health systems. [43][44][45][46] This leads to the first research question: What managerial know-how has helped augment the implementation of deinstitutionalization interventions?…”
Section: Research Questionsmentioning
confidence: 99%